2014
DOI: 10.1007/s12032-014-0411-z
|View full text |Cite
|
Sign up to set email alerts
|

CrkL regulates SDF-1-induced breast cancer biology through balancing Erk1/2 and PI3K/Akt pathways

Abstract: The adapter protein CrkL is required for regulating the malignant potential of human cancers. However, the regulatory mechanisms of CrkL on the stromal cell-derived factor 1 (SDF-1)/CXCR4 signaling pathways in breast cancer are not well characterized. Here, CXCR4 and CrkL proteins were tested in breast cancer cell lines and 60 primary breast cancer tissues. In vitro, the roles of CrkL in SDF-1-induced MDA-MB-231 cell cycle, invasion and migration were investigated. In the present study, CXCR4 and CrkL were hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Although many of the patients harbor the standard breakpoints covering ∼600 kb, a genomic space occupied by over 25 known genes, the CNVs of some GU patients were smaller and therefore more informative. Collectively the only gene within the minimal linear region of maximum CNV overlap is MAZ transcription factor, described in the literature as a simple housekeeping gene (38,39) but whose expression is known to influence the expression of other transcription factors (42,54,55). In addition to being the only gene occupying the 16p11.2 GU minimal region, MAZ has an exceptionally high haploinsufficiency rating (pLI score) of 0.95 according to the ExAC database of ∼61,000 individual genomes, meaning that the observed allele frequency for MAZ loss-of-function mutations is very low compared with what would be expected if MAZ were not haploinsufficient.…”
Section: Resultsmentioning
confidence: 99%
“…Although many of the patients harbor the standard breakpoints covering ∼600 kb, a genomic space occupied by over 25 known genes, the CNVs of some GU patients were smaller and therefore more informative. Collectively the only gene within the minimal linear region of maximum CNV overlap is MAZ transcription factor, described in the literature as a simple housekeeping gene (38,39) but whose expression is known to influence the expression of other transcription factors (42,54,55). In addition to being the only gene occupying the 16p11.2 GU minimal region, MAZ has an exceptionally high haploinsufficiency rating (pLI score) of 0.95 according to the ExAC database of ∼61,000 individual genomes, meaning that the observed allele frequency for MAZ loss-of-function mutations is very low compared with what would be expected if MAZ were not haploinsufficient.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies have reported that multiple aberrantly expressed genes in endometrial carcinoma could contribute to the malignant behavior (15,2124), novel markers that are able to identify tumor progression and predict the aggressive phenotype are still urgently required. Upregulation of CRKL expression has been implicated in several human cancers, including breast cancer, lung cancer and pancreatic cancer (15,16,25,26), where it leads to increased proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has verified CRKL as a promoting factor in multiple cancer progress. CRKL participates in regulating the Erk1/2 and PI3K/Akt pathways and induces promotion of cell invasion and migration in breast cancer cells [29]; over-expression of CRKL significantly increases cell proliferation and invasion in two pancreatic cancer cell lines (Capan-2 and Bxpc-3), which suggests a promoting function of CRKL in pancreatic cancer [30]. In our previous research, CRKL was identified up-regulated in multiple GC cell lines, including MKN-45, SGC-7901 and MKN-2 cells [15].…”
Section: Discussionmentioning
confidence: 99%